2015
DOI: 10.1089/adt.2015.647
|View full text |Cite
|
Sign up to set email alerts
|

Drug Discovery Goes Three-Dimensional: Goodbye to Flat High-Throughput Screening?

Abstract: Immortalized cells, generated from two-dimensional cell culture techniques, are widely used in compound screening, lead optimization, and drug candidate selection. However, such cells lack many characteristics of cells in vivo. This could account for the high failure rates of lead candidates in clinical evaluation. New approaches from cell biology, materials science, and bioengineering are increasing the utility of three-dimensional (3D) culture. These approaches have become more compatible with automation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 19 publications
(35 reference statements)
0
59
0
Order By: Relevance
“…A similar approach tested in human liver organoids yielded promising results indicating that the organoid system was amenable to therapeutic testing [109]. Methods are being developed for drug discovery using high throughput testing in 3D cultures which could be applied to therapeutic testing in patient-derived organoids [110]. Finally, a retrospective study using prostate organoids found that the organoids derived from distinct patients displayed different responses to therapies which correlated with the observed genetics of each patient’s cancer [10], suggesting that therapeutic testing of organoids will have clinical benefit.…”
Section: Using Organoids For Personalized Medicinementioning
confidence: 99%
“…A similar approach tested in human liver organoids yielded promising results indicating that the organoid system was amenable to therapeutic testing [109]. Methods are being developed for drug discovery using high throughput testing in 3D cultures which could be applied to therapeutic testing in patient-derived organoids [110]. Finally, a retrospective study using prostate organoids found that the organoids derived from distinct patients displayed different responses to therapies which correlated with the observed genetics of each patient’s cancer [10], suggesting that therapeutic testing of organoids will have clinical benefit.…”
Section: Using Organoids For Personalized Medicinementioning
confidence: 99%
“…in situ imaging) to predict which spheroids are pre-organoids, then the early stages of culture could be efficiently engineered, possibly bypassing the initial morphogenesis events, to produce a higher yield of desirable pre-organoids and thus organoids. Such improvement is essential to making organoid platforms tractable for large-scale studies and commercial applications such as pharmacogenomic profiling, selecting hits from drug screens, and optimizing lead compounds (Boehnke et al, 2016;Gordon et al, 2015;Edmondson et al, 2014;Eglen and Randle, 2015). Increasing the efficiency of pre-organoid production increases the predictability of downstream studies and decreases their scale while reducing costs and wasted reagents.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to capture tumor heterogeneity makes organoids superior to traditional cancer cell lines (13,14). Therefore, organoids can be an excellent tool in the future for ex vivo drug screening to select targeted therapy (15,16). Testing therapeutic agents in preclinical 3D cell cultures may also help reduce unnecessary side-effects and might reduce treatment costs.…”
Section: Discussionmentioning
confidence: 99%